Arctic climate shifts drive rapid ecosystem responses across the West Greenland landscape - Saros, Jasmine E.; Anderson, Nicholas John; Juggins, Stephen; McGowan, Suzanne; Yde, Jacob C.; Telling, Jon; Bullard, Joanna E.; Yallop, Marian L.; Heathcote, Adam J.; Burpee, Benjamin T.; Fowler, Rachel A.; Barry, Christopher D.; et al. (My University, 2019)
Prediction of high latitude response to climate change is hampered by poor understanding of the role of nonlinear changes in ecosystem forcing and response. While the effects of nonlinear climate change are often delayed or dampened by internal ecosystem dynamics, recent warming events in the Arctic have driven rapid environmental response, raising questions of how terrestrial and freshwater systems in this region may shift in response to abrupt climate change. We quantified environmental responses to recent abrupt climate change in West Greenland using long-term monitoring and paleoecological reconstructions. Using >40 years of weather data, we found that after 1994, mean June air temperatures shifted 2.2 degrees C higher and mean winter precipitation doubled from 21 to 40 mm; since 2006, mean July air temperatures shifted 1.1 degrees C higher. Nonlinear environmental responses occurred with or shortly after these abrupt climate shifts, including increasing ice sheet discharge, increasing dust, advancing plant phenology, and in lakes, earlier ice out and greater diversity of algal functional traits. Our analyses reveal rapid environmental responses to nonlinear climate shifts, underscoring the highly responsive nature of Arctic ecosystems to abrupt transitions.
Keywords: abrupt climate change; arctic; nonlinear; ecosystems